MODEL MATEMATIKA UNTUK MENENTUKAN NAMA HARI PADA SIKLUS TUJUH, LIMA DAN TIGAPULUH LIMA HARI PADA KALENDER GREGORIAN DI INDONESIA - Agung Prabowo; Sukono; Mustafa Mamat (LPPM Universitas Terbuka, 2021)
In the Javanese calendar (Anno Javanica) there are two types of day names, namely saptawara and pancawara. Pancawara is a five-day cycle (Legi, Paing, Pon, Wage and Kliwon). Saptawara is a seven day cycle, like the weekly cycle on the Gregorian Calendar (Monday, Tuesday, Wednesday, Thursday, Friday, Saturday and Sunday). The Gregorian calendar does not recognize the pancawara cycle. However, the use of the Gregorian Calendar in Indonesia combines a seven-day cycle with a five-day cycle so that there are names for Monday-Legi, Tuesday-Paing and so on. The result is a 35-day combination called selapanan. With the literature review method, a mathematical model will be built to determine the names of saptawara, pancawara and selapanan days for certain dates on the Gregorian calendar. Furthermore, these mathematical models will be called the saptawara model (four models), the pancawara and the selapanan model (two models respectively).